Pemetaan Desain Kemasan Produk UMKM Makanan: Analisis Visual di Toko Oleh-Oleh Bandung Berdasarkan Jenis, Bentuk, Material, dan Teknik Cetak - Yudiarti, Diena; Prabawa, Bijaksana; Swasty, Wirania; Salsabila, Salma Alya (Universitas Komputer Indonesia, 2024)
Improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the food sector, especially in the city of Bandung, is an ongoing challenge. One key aspect that can enhance the competitiveness of food MSMEs is effective product packaging design. However, MSMEs often face obstacles in creating packaging designs that align with market trends due to limited resources. Therefore, this research aims to conduct a mapping of packaging designs for food MSMEs in souvenir shops in Bandung, focusing on the types of designs, shapes, materials, and printing techniques used. This study employs a qualitative descriptive approach with observational methods, analyzing visual data. The results reveal that the majority of packaging consists of primary packaging, featuring folding carton and stand-up pouch forms, primarily utilizing offset printing and direct print decorations. The most frequently used material is cardboard. This research can serve as a guide for MSMEs in the Bandung region to innovate their packaging designs. The findings are expected to contribute to enhancing the competitiveness of food MSMEs in Bandung and its surrounding areas.